Prevalence and Nondisclosure of Complementary and Alternative Medicine Use in Patients With Cancer and Cancer Survivors in the United States - Sanford, Nina N. (JAMA Oncol, 2019)
This cross-sectional study analyzes the proportion of patients with cancer and cancer survivors who use complementary and alternative medicine (CAM) without disclosing this information to their physicians.